Electroacupuncture Reduces Visceral Pain Via Cannabinoid CB2 Receptors in a Mouse Model of Inflammatory Bowel Disease - Zhang, Hong; He, Wei; Hu, Xue-Fei; Li, Yan-Zhen; Liu, Yong-Min; Ge, Wen-Qiang; Zhanmu, Ou-Yang; Chen, Chao; Lan, Yu-Ye; Su, Yang-Shuai; Jing, Xiang-Hong; Zhu, Bing; et al. (Frontiers in Pharmacology, 2022)
Inflammatory bowel disease (IBD) results in chronic abdominal pain in patients due to the presence of inflammatory responses in the colon. Electroacupuncture (EA) is effective in alleviating visceral pain and colonic inflammation associated with IBD. Cannabinoid CB2 receptor agonists also reduce colonic inflammation in a mouse model of IBD. However, whether EA reduces visceral pain and colonic inflammation via the CB2 receptor remains unknown. Here, we determined the mechanism of the analgesic effect of EA in a mouse model of IBD induced by rectal perfusion of 2,4,6-trinitrobenzenesulfonic acid solution (TNBS). EA or sham EA was performed at the bilateral Dachangshu (BL25) point for 7 consecutive days. The von Frey and colorectal distension tests were performed to measure mechanical referred pain and visceral pain. Western blotting and immunohistochemistry assays were carried out to determine the expression of IL-1β and iNOS and activation of macrophages in colon tissues. We found that EA, but not sham EA, attenuated visceral hypersensitivity and promoted activation of CB2 receptors, which in turn inhibited macrophage activation and the expression of IL-1β and iNOS. The effects of EA were blocked by AM630, a specific CB2 receptor antagonist, and by CB2 receptor knockout. Our findings suggest that EA attenuates mechanical allodynia and visceral hypersensitivity associated with IBD by activating CB2 receptors and subsequent inhibition of macrophage activation and expression of IL-1β and iNOS.